John D. Whiting papers - Whiting, John D. (John David), 1882-1951
Correspondence, diaries, notebooks, reports, subject file, film catalogs and caption lists, printed matter, photographs, and other papers pertaining to Whiting's life as a prominent member of the American Colony in Jerusalem, a Christian utopian community founded in 1881. Documents Whiting's work as a business manager and artifact dealer with Fr. Vester & Co., also known as the American Colony Store; tour guide of historic sites in the Middle East; photographer with the American Colony Photo Dept.; author and photographer published in National Geographic; deputy U.S. consul for Jerusalem; and military intelligence officer for the British Army during World War I. Subjects include Jacob Spafford's discovery of the inscription in Hezekiah's Tunnel, Jerusalem; the locust plague of 1915; conditions in Jerusalem during World War I; the Arab-Israeli conflict; industry and commerce in the region; and Whiting family life. Family members represented include Anna T. Spafford, Jacob Spafford, Bertha Spafford Vester, Alice Brauch Whiting, Edmund Wilson Whiting, and Grace Spafford Whiting.
Library of Congress Prints and Photographs Division.
Businessman, photographer, author, tour guide, and intelligence officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Spafford, Anna T., -- 1842-1923.; Spafford, Jacob; Vester, Bertha Spafford, -- 1878-1968.; Whiting, Alice Brauch; Whiting, Edmund Wilson; Whiting, Grace Spafford; Whiting family; Great Britain. -- Army -- Intelligence specialists; American Colony (Jerusalem); American Colony (Jerusalem). -- Photo Department; Fr. Vester & Co; National geographic magazine; Americans -- Jerusalem; Arab-Israeli conflict -- 1948-1967.; Christian communities -- Jerusalem; Communal living -- Jerusalem; Diplomatic and consular service, American -- Jerusalem; Historic sites -- Middle East; Industries -- Middle East; Industries -- Palestine; Locusts -- Middle East; Missionaries -- Jerusalem; Missionaries -- United States; Photography -- Middle East; World War, 1914-1918 -- Military intelligence -- Great Britain; World War, 1914-1918 -- Jerusalem; Hezekiah's Tunnel (Jerusalem); Jerusalem -- Commerce; Jerusalem -- History; Jerusalem -- History -- Siege, 701 B.C.; Middle East -- Antiquities; Middle East -- Commerce; Middle East -- Description and travel; Middle East -- History; Palestine -- Commerce; Palestine -- Foreign relations -- United States; Palestine -- History; United States -- Foreign relations -- Palestine; Authors; Businessmen; Intelligence officers; Photographers; Tour guides